(untitled) (Philology, 2024)
The text is an analysis of the novel Chance and vice versa by the contemporary Spanish writer Felipe Benítez Reyes. The author of the study defends the thesis that the picaresque genre is not limited to the Spanish Golden Age, but continues to exist throughout the centuries up to the present day. The aim is to demonstrate that the work belongs to the genre of the picaresque novel by examining the characteristics of the protagonist’s personality, his way of being and thinking and his relations with the surrounding world in order to highlight the features that he shares with the traditional image of the pícaro, as well as those that confer originality and constitute the novelist’s main contribution to the genre. In the second part, stylistic features are examined to demonstrate their affinity with baroque conceptismo.